Clinical practices of the management of nonvalvular atrial fibrillation and outcome of treatment: A representative prospective survey in tertiary healthcare centers across Turkey - Ozin, Bulent; Aytemir, Kudret; Aslan, Ozgur; Ozcan, Turkay; Kanadasi, Mehmet; Demir, Mesut; Oto, Ali (Kare Publ, 2018)
Objective: The goal of this study was to define clinical practice patterns for assessing stroke and bleeding risks and thromboprophylaxis in nonvalvular atrial fibrillation (NVAF) and to evaluate treatment outcomes and patient quality of life. Methods: A clinical surveillance study was conducted in 10 tertiary healthcare centers across Turkey. Therapeutic approaches and persistence with initial treatment were recorded at baseline, the 6th month, and the 12th month in NVAF patients. Results: Of 210 patients (57.1% male; mean age: 64.86 +/- 12.87 years), follow-up data were collected for 146 patients through phone interviews at the 6th month and 140 patients at the 12th month. At baseline, most patients had high CHADS(2) score (>= 2: 48.3%) and CHA(2)DS(2)-VASc (>= 2: 78.7%) risk scores but a low HAS-BLED (0-2: 83.1%) score. Approximately two-thirds of the patients surveyed were using oral anticoagulants as an antithrombotic and one-third were using antiplatelet agents. The rate of persistence with initial treatment was approximately 86%. Bleeding was reported by 22.6% and 25.0% of patients at the 6th and 12th month, respectively. The proportion of patients with an INR of 2.0-3.0 was 41.8% at baseline, 65.7% at the 6th month, and 65.9% at the 12th month. The time in therapeutic range was 61.0% during 1 year of follow-up. The median EuroQol 5-dimensional health questionnaire (EQ-5D) score of the patients at baseline and the 12th month was 0.827 and 0.778, respectively (p<0.001). The results indicated that patient quality of life declined over time. Conclusion: In atrial fibrillation, despite a high rate of persistence with initial treatment, the outcomes of stroke prevention and patient quality of life are not at the desired level. National health policies should be developed and implemented to better integrate international guidelines for the management of NVAF into clinical practice.
Keywords: Anticoagulants; atrial fibrillation; quality of life in atrial fibrillation; treatment outcome in atrial fibrillation; warfarin